Residual effects of low dose of suvorexant, zolpidem, and ramelteon in healthy elderly subjects: A randomized double‐blind study. Issue 3 (24th June 2022) - Uemura, Sachiko Ito; Imanishi, Aya; Terui, Yoshino; Park, Insung; Satake, Masahiro; Han, GoEun; Shioya, Takanobu; Kanbayashi, Takashi; Nishino, Seiji
Abstract: Introduction: Current hypnotic agents have next‐day residual effects. The new orexin antagonist, suvorexant, has little muscle relaxation effect on the physical and cognitive function in the following morning and daytime. In this study, the effects of suvorexant, zolpidem, ramelteon and placebo in elderly subjects were evaluated. Methods: Six men and eight women aged 63–75 years received a single tablet and lights were then turned off. Subjects were instructed to sleep from 23:00–6:00 with an interruption from 4:00–4:30 for evaluations. Suvorexant 10 mg, zolpidem 5 mg, ramelteon 4 mg or placebo was administered single time in a randomized, double‐blind and crossover design with a one‐week drug holiday in between each drug. Measures of objective parameters and subjective ratings were obtained every 2 h from 4:00 to 16:00. Result: No subjects showed serious side effects from physical observations and vital sign checks before and after hypnotics were taken. During the first sleep period, the REM sleep time with suvorexant was especially longer than that with zolpidem. During the second sleep period, suvorexant had shorter sleep latency and longer stage2 sleep time than ramelteon and zolpidem, respectively. During the whole entire sleep, the REM sleep time with suvorexant was longer than zolpidem and placebo. For the body sway test with closed eye, the main effects of the medicines and zolpidem were significantly better than suvorexant and ramelteon. Conclusion: The changes of physical and cognitive functions in healthy elderly after taking hypnotics were not remarkable. Therefore, these three hypnotics maybe appropriate for the elderly people with insomnia for single‐time low dose administration.